HUBUNGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PERAWAT DENGAN KUALITAS PELAYANAN KEPERAWATAN PADA MASA PANDEMI COVID-19 DI RSUD DEPOK - Dinda Nur Aini (2022)
The COVID-19 pandemic has had a major impact on hospital institutions, which are organizations that are facilitated by health services, especially nurses as the frontline who have a major role in determining the quality of nursing services. Organizational citizenship behavior is a nurse's voluntary behavior at work which has several dimensions. The purpose of this study was to analyze the relationship between nurses' organizational citizenship behavior and the quality of nursing services during the COVID-19 pandemic at the Depok Hospital. This study used a correlational analytic descriptive research design using a cross-sectional approach and a total sampling technique with a total sample of 60 nurses. Collecting data using a questionnaire and analyzed using the Chi-Square Test. The results of statistical tests showed that there was a relationship between altruism (p=0.035), conscientiousness (p=0.000), sportsmanship (p=0.002), courtesy (p=0.000), civic virtue (0.001), and organizational citizenship behavior of nurses (p= 0.000) with the quality of nursing services. The concludes that there is a relationship between organizational citizenship behavior and the quality of nursing services. Recommendations for further researchers can research the comparison of organizational citizenship behavior with the quality of nursing services during the COVID-19 pandemic and after the COVID-19 pandemic.